Investigation of development possibilities in Gödöllő - Némediné Kollár, Kitti; Kovács, Petra (Studia Mundi – Economica, 2023)
A general trend has emerged in recent years that the importance of cities and settlements located in the Budapest agglomeration for the choice of residence is increasing. More and more people are moving to agglomeration settlements surrounding Budapest (mostly from the capital), which has also been strongly influenced by the COVID-19 pandemic situation. Gödöllő is still a popular destination among the population moving in. However, there is a significant territorial difference in the level of development of agglomeration settlements. Overall, Gödöllő is a developed city based on competitiveness rankings. Gödöllő is located in Budapest and the eastern gate of its agglomeration, which has a serious regional role. It is also a defining district seat and a popular place of residence for those moving out of the capital. It also has a significant impact on the surrounding smaller settlements and rural settlements, with many commuting daily to work or even leisure. In this research we were interested in how developed Gödöllő is in terms of economic and social indicators and what further development opportunities lie in the town? In our research, we set ourselves the goal of presenting the importance of Gödöllő based on the selected indicators, assessing the level of development and examining its further development opportunities. Based on the results of this research, we formulated the greater use of the potential and the future strategic development directions.